Application of a Collaborative Learning Model Accompanied by Quantum Learning Strategies in Improving Class VIII Science Biology Learning Outcomes at Junior High School 2 Satap Balla - Rasjid, Yusniar; Bahar, Irnayanti (PT ARRUS Intelektual Indonesia, 2023)
This research is a Classroom Action Research (PTK) which aims to find out whether the application of a collaborative learning model accompanied by a quantum learning strategy can improve student learning outcomes in class VIII SMP Negeri 2 Satap Balla. The subjects of this study were class VIII students of SMP Negeri 2 Satap Balla in the odd semester of the 2022/2023 school year with a total of 24 students, with details of 15 male students and 9 female students. Cycle I and cycle II were held in four meetings each including giving tests. Data collection was carried out using student learning outcomes tests at the end of each cycle, and observations at each meeting. Data were analyzed using quantitative descriptive analysis. The results showed that in the first cycle the average value was 68.33 with the completeness of class 9 students (37.5%), and the average in the second cycle was 86.66 with the completeness of the class of 21 students (87.5%) . It can be concluded that the application of a collaborative learning model accompanied by a quantum learning strategy can improve learning outcomes in class VIII Biology at SMP Negeri 2 Satap Balla.